ANALISIS KADAR KALSIUM (Ca) DAN MAGNESIUM (Mg) PADA KACANG METE (Anacardium occidentale.L) SECARA SPEKTROFOTOMETRI SERAPAN ATOM - Rais Razak (As-Syifaa Jurnal Farmasi, 2010)
Analysis of Calsium (Ca) and magnesium (Mg) in the mete nut (Anacardium occidentale L.) by Atomic Absorption spectrophotometry. This research intended to determine rates  of calsium (Ca) and magnesium (Mg) in the mete nut (Anacardium occidentale L.) by means of Atomic Absorption Spectrofotometry. The research enwrap qualitative analysis. Before to be analised, first to do destruction mete nut (Anacardium occidentale L.) later on dissolved in HNO3 and HCl. Qualitative analysis used  specific reactant and quantitative analysis used atomic absortion spectrophotometry at wave length of 422,7 nm and 285,21 nm for calsium and magnesium respectively. The result of the research indicated that average rates of calsium in the mete nut (Anacardium occidentale L.) is 1055,83 mg/100 g of the sample. Average rates of  magnesium in the mete nut (Anacardium occidentale L.) is 58 mg/100 g of the sample.Key Words : Calsium (Ca) and magnesium (Mg) and Anacardium occidentale L